Susceptibility of the Punctulatus group (Diptera: Culicidae) to insecticide carbamate in Papua, Indonesia - LEPA SYAHRANI; ASTARI DWIRANTI; PUJI BUDI SETIA ASIH; ISMAIL EKOPRAYITNO ROZI; DENDI HADI PERMANA; ANOM BOWOLAKSONO; DIN SYAFRUDDIN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Syahrani L, Dwiranti A, Asih PBS, Rozi IE, Permana DH, Bowolaksono A, Syafruddin D. 2025. Susceptibility of the Punctulatus group (Diptera: Culicidae) to insecticide carbamate in Papua, Indonesia. Biodiversitas 26: 1376-1383. Insecticide Treated Nets (ITNs) and Indoor Residual Spraying (IRS) are the primary vector control tools recommended for reducing malaria transmission in endemic areas. However, the emergence and spread of pyrethroid resistance among the Anopheles punctulatus group poses a significant challenge for malaria vector control in Papua, Indonesia. While carbamate-based IRS is a potential strategy to mitigate resistance, its effectiveness within malaria control programs requires continuous monitoring. This study assessed the susceptibility of the Punctulatus group to bendiocarb (0.1%) and analyzed the underlying resistance mechanisms. Bioassays were conducted in three sub-districts of Keerom District, Papua. Additionally, biochemical assays were performed to measure the activity of detoxifying enzymes, including esterases, Glutathione S-Transferases (GSTs), and acetylcholinesterase. Ace-1 fragments were amplified using Polymerase Chain Reaction (PCR), followed by sequencing to detect nucleotide substitution at codon 119. Results indicated full susceptibility (100%) of the Punctulatus group to bendiocarb at all study sites. Compared to unexposed controls, bendiocarb-exposed populations exhibited significantly higher GST (p: 1.403e-06), elevated esterase activity (p: 0.247), and reduced acetylcholinesterase inhibition (p: 0.002). PCR sequencing of 29 samples confirmed that all carried the wild-type Ace-1 allele (GGG, GGC, and GGT). These findings provide crucial evidence for malaria control programs in selecting appropriate vector control products and managing insecticide resistance. Despite full susceptibility to bendiocarb, elevated detoxification enzyme activity suggests potential early-stage metabolic resistance. Further molecular studies are recommended to investigate metabolic resistance mechanisms, along with rigorous monitoring using bioassays, biochemical assays, and molecular tools to track insecticide susceptibility trends over time.